Lubomír Doležel and Aesthetics - Fořt, Bohumil (Bohemica Olomucensia, 2024)
The study focuses on the aesthetic dimensions of the work of Lubomír Doležel. This work, although essentially bound to the field of literary theory, displays various links to aesthetic categories and connects them to linguistic, semiotic, literary and narrative theoretical and other of the author's findings. The study reveals these connections.
Keywords: Lubomír Doležel; aesthetic; literary theory